2017
DOI: 10.2320/matertrans.mk201633
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide (CO<sub>2</sub>) Released in the Electrochemical Reduction of Titanium Dioxide (TiO<sub>2</sub>) to Titanium Metal

Abstract: Studies pertaining to kinetic aspects of the direct electrochemical reduction process of titanium preparation from TiO 2 have not been substantial for determining the conversion time precisely. The solid state reduction process does not permit measuring either the rate of formation of product or the rate of depletion of the feed stock. In this work an attempt has been made to study the applicability of variation of CO 2 (the product gas) in the vent gases of the electrolytic cell to approximate the bulk proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…La presencia de oxígeno enlazado con silicio se observa en la señal 2240 cm -1 como Ox-Si-H y en la región de 3350-3700 cm -1 corresponde a la vibración de los grupos hidroxilo O-H de tipo estiramiento (Losic, D.;, la forma del espectro IR en la región de 1000-1200 cm -1 es característica de silicio poroso oxidado (Lee, B., 2011;Losic, D.;. Se propone que, durante el proceso de obtención del material se forma la estructura porosa en el silicio cristalino y el óxido de titanio se coloca en forma de aglomerados en la superficie de este, distribuido de manera aleatoria, además el oxígeno presente reacciona para dar lugar a enlaces del tipo Ox-Si-H, SiHx y Si-OH (Gregorio Vázquez, L., 2013;Rajulu, G., 2017). El espectro de fotoluminiscencia (Fig.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…La presencia de oxígeno enlazado con silicio se observa en la señal 2240 cm -1 como Ox-Si-H y en la región de 3350-3700 cm -1 corresponde a la vibración de los grupos hidroxilo O-H de tipo estiramiento (Losic, D.;, la forma del espectro IR en la región de 1000-1200 cm -1 es característica de silicio poroso oxidado (Lee, B., 2011;Losic, D.;. Se propone que, durante el proceso de obtención del material se forma la estructura porosa en el silicio cristalino y el óxido de titanio se coloca en forma de aglomerados en la superficie de este, distribuido de manera aleatoria, además el oxígeno presente reacciona para dar lugar a enlaces del tipo Ox-Si-H, SiHx y Si-OH (Gregorio Vázquez, L., 2013;Rajulu, G., 2017). El espectro de fotoluminiscencia (Fig.…”
Section: Resultados Y Discusiónunclassified
“…La energía de banda prohibida obtenida de la caracterización de fotoluminiscencia se puede relacionar con el tamaño de los cristalitos de silicio mediante la ecuación E1, la cual toma en cuenta la energía de bulto y el parámetro de confinamiento (𝐸 𝑁 = 𝐸 𝑏𝑢𝑙𝑘 + ( 𝐶 𝑑 2 )). Donde d1 es el diámetro de la partícula y se asigna para alambres cilíndricos de silicio (Rajulu, G., 2017;Lin, G., 2005;Deleure, C., 1993). Así, el valor obtenido para 𝑑 1 = 3.0 𝑛𝑚.…”
Section: Resultados Y Discusiónunclassified
“…Since the discovery of the process several developments/advancements has been taking place for an improved understanding of the mechanism of metallization, scaling up, enhanced product purity, applying process for alloy preparation and exploiting the principle for other possible metal oxides, etc. Basic research carried out at DMRL attempted to bring in an improved understanding of the reaction mechanism and the importance of monitoring CO 2 content in the vent gases [14,15]. Excellent reviews by Mohan Das [16,17] bring out details of developments that have been taking place in the FFC process over the years.…”
Section: The Ffc (Fray Farthing and Chen) Processmentioning
confidence: 99%
“…In 2017, Ono et al 28) showed the experiences of the industrial model of the OS process, where a 10-day campaign was conducted with 2 tons of molten salt and a current of 4000 A. Rajulu et al 29) in India studied the kinetic aspects of direct electrochemical reduction using 0.51.0 kg TiO 2 in 58 kg cells. The CO 2 (product gas) concentration in the vent gas during electrolysis followed a trend similar to the DC current, as shown in Fig.…”
Section: Applicability At Industrial Levelmentioning
confidence: 99%
“…1 Variation of electrolysis current and CO 2 concentration in vent gas with time (58 kg batch). 29) optimizing the cooling conditions, the CaO content in the molten salt, TiO 2 particle size, and dehydration methods of salt, an industrial level of 0. . The existence of a small amount of water in CaCl 2 causes rapid electrodeposition due to water impurities, resulting in low electrolysis efficiency.…”
Section: Optimization Of Os Process Parametersmentioning
confidence: 99%